THE EFFECT OF BRAIN GYM TO THE LEVEL OF DEPRESSION IN GERIATRIC AT BALAI PERLINDUNGAN SOSIAL TRESNA WERDHA CIPARAY BANDUNG - Andria Pragholapati (Fakultas Ilmu Keperawatan Universitas Advent Indonesia, 2019)
Introduction: World Health Organization data (2010) showed the world population geriatric affected by depression as many as 7 million people. Increasing in the geriatric lived in institutions around 50-75%. The purpose: of this study to determine the effect of Brain Gym on the level of depression in the geriatric in Balai Perlindungan sosial Tresna Werdha Ciparay Bandung 2016. This study was a experimental quasy pre-post test with a control group. The sample in this study as many as 34 people were divided into two groups of 17 people each.the sample used is purposive sampling that meet the inclusion and exclusion criteria. Brain Gym was given to the treatment group 9 times in 5 days. The questionnaire used Geriatric Depression Scale Short form that had a value of Cronbach Alfa 0960 ≥ 0632 declared valid and reliable questionnaire. Data were analyzed using the Wilcoxon test and Mann Whitney test. Results: Wilcoxon show was only the intervention group there are differences in the level of depression with p value in the control group 0.109 (α 0.05) and p value 0.000 in the intervention group (α 0.05). Results of mann whitney in both groups was obtained p value 0.000 (α 0.05), then Ho was rejected,this shows Brain Gym No Effect On The Level Depression. Discussion: Based on the results of the study states that Brain Gym can reduce the level of depression in the geriatric so important examination in geriatric depressed levels regulary and applied Brain Gym movements to reduce the level of depression in the geriatric.